Implementation Of An Islamic Religious Education Learning Model Based On Students’ Economic Independence At SMA Ma’arif Sukorejo - Mahbubah El Gabriela; Ahmad Ma’ruf; Ali Mohtarom; M. Jamhuri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to determine the model and implementation of Islamic Religious Education (PAI) based on economic independence at SMA Ma’arif Sukorejo and its influence on the development of students’ character and independence. This research employed a qualitative approach with a descriptive research type to gain an in-depth understanding of the learning process implemented at the school. Data sources were obtained from PAI teachers, students, documentation, and learning materials, while data collection techniques were conducted through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, while data validity was tested through source and method triangulation. The results showed that the PAI learning model based on economic independence was developed through the integration of muamalah materials and Islamic business ethics with simple business practices such as class bazaars and student entrepreneurship activities. The implementation of this learning model was able to instill Islamic values such as honesty, trustworthiness, discipline, responsibility, hard work, and gratitude, as well as improve students’ independence in managing finances, making decisions, and facing business risks. Although there were obstacles in balancing school activities and business practices, practice-based learning provided meaningful learning experiences that were relevant to students’ socio-economic lives.